A função do professor na proposta educacional de John Dewey (1859-1952) - Souza , Helton Adriano de (2019)
The goal of this thesis was to analyze John Dewey‘s (1859-1952) educational philosophy and pedagogical method, especially the teacher's role in the new generation formation. Starting from a historical-approach of the human phenomena, we place Dewey's thought in the context of the bourgeois way of production organization, institutions and science in the late 19th century and first half of the twentieth century. Facing the changes and contradictions that featured the development of industry, science and social life, especially those affecting the United States, the author pointed out the need to rethink education as well, reaching a special dimension in the education reform and, therefore, the role of the teacher. Dewey‘s books, The Child and the Curriculum; How We Think; Interest and Effort in Education; Democracy and Education, and Experience and Education, were our main bibliographic source. As secondary references, we have chosen the historiography, which deals with the historical-social context delimited by the research, and with Dewey's ideas. We emphasized that the author's thinking is an invitation to educators to carefully listen to the ongoing changes in order to establish for new generations new formative parameters in a democratic perspective. We have examined the author's conception of education and the relationship between teaching and learning as a life necessary process. We have shown Dewey's criticism to the traditional pedagogy and innovative educational theories, highlighting the elements that on the pedagogical practice, according to the author, did not promote a meaningful educational experience based on interaction and continuity, their basic principles. We have clarified the teacher's importance by exposing that, in Dewey's perspective, he or she is the one who leads the immature in the most complex and elaborate processes of reflective thinking and meaningful experience. Therefore, we verified that the author, in a context of social changes, gave a new meaning to the teacher's attributions by conducting the educational experience based on reflective thinking whose purpose was to form the new generations for sustaining a democratic life in a complex society. The teacher is the one who has the greatest mastery of the human experience and the technical-scientific knowledge corresponding to his or her métier in the school educational relationship. So, it would be up to him or her to control, direct and guide the student's formative process in order to favor the construction of his or her intellectual autonomy, enabling them to direct themselves and consequently the society in which, in principle, they are potential beings. We have concluded that Dewey's thought contributes to the current reflections on the teacher's role, not as a copy to be transposed to the pedagogical practices of our time, but read in the historical period that gave him social background, and, like so many other classic works, becoming a reference that alerts us, among other questions, about the importance of being mindful and involved with the formation of new generations. On that regard, besides being essential for his historical time, we believe that his legacy has gone through generations without losing scientific value and making him a classic author, which allows us to reflect on the complexity and contradictions of life, and thereby of education and pedagogy during history, linking past, present and future